Determinación de la dureza de agua de consumo humano de la parroquia Simiatug, cantón Guaranda, provincia de Bolívar periodo 2013-2014 - Caiza Chanaguano, Walter Pachacutic (2014)
Water is the substance more abundant on earth, which represents is ideal medium for life. They hydrologic cycle determines the state in which it find: liquid in rain, rivers, oceans, as solids is insnow and asgas is in clouds. The quality of this resource depends on natural factors and human activity. They use of water in different activities does that changes they bacteriological and biological, chemical physical characteristics affecting seriously the existence of the life ecosystems. The present research is aimed at the determination the hardness of water in the parish water distribution system. The Calcium and Magnesium are causing temporary hardness minerals, have their origin in the calcareous rock formations, and can be jocund is greater or less degree, in the majority of natural waters. The chloride, sulfides, phosphates and nitrates is induced in permanent hardness is caused by agriculture, cattle industrialization and urban settlement, with highly polluting effluents….